Porosity and mechanical properties of zirconium ceramics; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Kalatur E. Ekaterina; Buyakova S. P. Svetlana Petrovna; Kulkov S. N. Sergey Nikolaevich; Narikovich A. Anton (2014, 2014)
Title screen